2012
DOI: 10.1016/j.ajpath.2012.05.021
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and Olfactory Cytotoxicity of Inhaled 2,3-Pentanedione in Sprague-Dawley Rats

Abstract: Flavorings-related lung disease is a potentially disabling disease of food industry workers associated with exposure to the α-diketone butter flavoring, diacetyl (2,3-butanedione). To investigate the hypothesis that another α-diketone flavoring, 2,3-pentanedione, would cause airway damage, rats that inhaled air, 2,3-pentanedione (112, 241, 318, or 354 ppm), or diacetyl (240 ppm) for 6 hours were sacrificed the following day. Rats inhaling 2,3-pentanedione developed necrotizing rhinitis, tracheitis, and bronchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(124 citation statements)
references
References 85 publications
4
112
0
3
Order By: Relevance
“…14 Toxicological studies in animals have shown that it has adverse effects on respiratory epithelium similar to DA and at similar levels. 15,28 Study Implications A wide range of DA and AP concentrations were found in the samples, indicating that in some cases the chemicals were used deliberately as ingredients while in others they were probably contaminants. Overall the estimated daily exposure from EC use was approximately 100 times lower for DA and 10 times lower for AP compared to tobacco cigarettes; therefore, it is still plausible to classify ECs as tobacco harm reduction products.…”
Section: Toxicity Of Da and Apmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Toxicological studies in animals have shown that it has adverse effects on respiratory epithelium similar to DA and at similar levels. 15,28 Study Implications A wide range of DA and AP concentrations were found in the samples, indicating that in some cases the chemicals were used deliberately as ingredients while in others they were probably contaminants. Overall the estimated daily exposure from EC use was approximately 100 times lower for DA and 10 times lower for AP compared to tobacco cigarettes; therefore, it is still plausible to classify ECs as tobacco harm reduction products.…”
Section: Toxicity Of Da and Apmentioning
confidence: 99%
“…Unfortunately, the risks associated with inhalation of AP may well be as high as from DA, based on inhalation studies performed on rats. 15 Due to the potential hazards associated with inhalation exposure to DA and AP, regulatory agencies have set specific Occupational Exposure Limits (OELs 10,16 For AP, NIOSH has set a TWA limit of 9.3 ppb (38 µg/m 3 ) and an STEL of 31 ppb (127 µg/m 3 ). 10 The purpose of this study was to examine the presence of DA and AP in a large sample of EC liquids obtain from European and US manufacturers and retailers.…”
Section: Introductionmentioning
confidence: 99%
“…Mice were exposed in a glass and stainless steel whole-body inhalation exposure chamber, as previously described for diacetyl and 2,3-pentanedione exposures in rats but modified for exposing mice. 3,16 In brief, a computer-controlled syringe pump injected diacetyl into stainless steel tubing, which was heated to 150 C. Diluent air flowed through the tubing so that the air in the tubing was at 70 C when the diacetyl was vaporized and then flowed into the inhalation chamber, where the concentration was monitored using a volatile organic compound meter (PGM-760; RAE Systems, San Jose, CA). The temperature in the chamber was maintained between 27.0 C and 28.0 C. Each mouse was housed individually in a wire cage during the exposures.…”
Section: Protein Damage and Diacetyl Cytotoxicitymentioning
confidence: 99%
“…For the immunofluorescence assays, antigenicity was retrieved with 1 mmol/L EDTA, as previously described. 16 Slides were then rinsed in distilled water and blocked for 2 hours at room temperature using 10% donkey serum (Jackson ImmunoResearch). Primary antibodies were applied using capillary action with pairs of ProbeOn Plus slides (Fisher Scientific, Pittsburgh, PA), which were incubated overnight at 4 C. Nonimmune serum or immunoglobulin was used in place of the primary antibodies in the negative control slides.…”
Section: Fluorescence Assaysmentioning
confidence: 99%
See 1 more Smart Citation